1972
DOI: 10.1104/pp.50.5.572
|View full text |Cite
|
Sign up to set email alerts
|

Aftereffects of Low and High Temperature Pretreatment on Leaf Resistance, Transpiration, and Leaf Temperature in Xanthium

Abstract: Leaf resistance for water vapor (total diffusion resistance minus boundary layer resistance), transpiration, and leaf temperature were measured in attached leaves of greenhouse-grown Xanthium strumarium L. plants that had been pretreated for 72 hours with high (40 C day, 35 C night), or low (10 C day, 5 C night) air temperatures. Measurements were made in a wind tunnel at light intensity of 1.15 cal cm-2 min-', air temperatures between 5 and 45 C, and wind speed of 65 cm sec1. Leaf resistances in low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

1974
1974
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 12 publications
1
19
0
3
Order By: Relevance
“…Figure 4 shows that at any intercellular CO2 concentration (except below 200 /A 1-' in leaves prechilled for 24 hr) stomatal conductance decreased with increasing duration of the chilling treatment. Drake and Salisbury (1) showed that stomata in prechilled leaves did not open as wide at any subsequent temperature between 5 and 45 C as did stomata in unchilled leaves. Tschape (14) observed that stomata responded sluggishly after chilling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 shows that at any intercellular CO2 concentration (except below 200 /A 1-' in leaves prechilled for 24 hr) stomatal conductance decreased with increasing duration of the chilling treatment. Drake and Salisbury (1) showed that stomata in prechilled leaves did not open as wide at any subsequent temperature between 5 and 45 C as did stomata in unchilled leaves. Tschape (14) observed that stomata responded sluggishly after chilling.…”
Section: Discussionmentioning
confidence: 99%
“…higher at the end of a 6-hr exposure to 25 C than 1 Stomatal Conductance in Relation to the Intercellular CO2 Concentration. In the control leaves, stomata hardly responded to changes in ambient and intercellular CO2 concentration.…”
Section: Decreases In Net Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, incrementos no metabolismo podem ser indiretamente aferidos em função da temperatura da folha. Normalmente essa diferença fica em torno de um ou dois graus, mas em casos extremos pode exceder a 5 o C (Drake & Salisbury, 1972;Atkin et al, 2000). A temperatura da folha das plantas de arroz não foi alterada em função do aumento na intensidade de competição com plantas de capim-arroz do biótipo resistente ao herbicida (Tabela 4).…”
Section: Resultsunclassified
“…Assim, incrementos no metabolismo podem ser indiretamente aferidos em função do gradiente entre temperatura da folha e do ar (T). Normalmente ess a diferença é de somente um ou dois graus, mas, em casos extremos, pode exceder 5 o C (Drake & Salisbury, 1972;Atkin et al, 2000). Uma vez que a  T não mostrou significância estatística, pode-se concluir que o metabolismo não foi seriamente afetado e que esse fator provavelmente possa ser excluído da participação na Gs.…”
Section: Resultsunclassified